KOMPARASI MONOHULL DAN LAMBUNG KATAMARAN BENTUK CHINE PADA DAMPAK PERUBAHAN PERAIRAN DANGKAL - Dimas Yusuf Waskito, (2021)
Hull shape modifications are increasingly being investigated by varying the shape of the hull to get an optimum hull. Various modifications to the hull have been made, one the ways is by increasing the number of hulls to become multihull. In this study, a comparative study of monohull and chine hull catamarans was carried out on variations in the ratio of shallow water. Hull modeling using maxsurf, and analysis of the effect of squat, sinkage and trim using ansys AQWA Hydrodynamic Diffraction. Based on the simulation result on the squat effect, the katamaran hull has the most significant squat effect at an average of 20,69 % lower than monohull. While on the sinkage effect, the katamaran hull has the most significant sinkage effect at an average of 40,4 % when trim by stern, and when trim by bow is 34,21 % lower than monohull. And on the trim effect, the 10 % LCG change when trim by bow and trim by stern, on monohull and catamaran hulls produces the smallest sinkage effect. The effect of squat, sinkage, and trim, was very significant at the lowest depth condition, at H/T = 1.2. and it can be concluded that the catamaran model is safer when sailing in shallow waters compared to the monohull model.